Flexible Nets for the Optimization of IgG Production in CHO cells - Lázaro Ibáñez, Jorge; Joven, Teresa (Jornada de Jóvenes Investigadores del I3A, 2025)
Antibody production using CHO cells is ofteninefficient due to trial-and-error approaches. Toimprove this, we developed a mathematical modelbased on Flexible Nets that integrates cellmetabolism and bioreactor dynamics. Thismulti-scale modeling enables systematic, optimizeddesign of antibody manufacturing, enhancingproductivity while reducing time and cost.